How does the firm size affect the relative importance of country and industry effect in capital structure? Empirical evidence from Europe - Koralun-Bereźnicka, Julia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of this study is to determine the relative importance of the country and industry factors in the capital structure depending on the firm size. The analysis includes three size groups of firms in thirteen industries of nine EU countries and covers the period 2000-2009. The applied methods include multivariate statistical analysis, mainly the k-means cluster analysis. Findings reveal the prevalence of the country factors, although not homogeneously across all size groups
Argumenta Oeconomica, 2017, Nr 1 (38), s. 99-119
Keywords: capital structure; country effect; industry effect; firm size